Approximating Bending Stiffness for Structural Optimization of Double-skin Hollowed Car Body Panels - Yoshiki Ohta (EPI International Journal of Engineering, 2018)
This paper presents the construction of the approximate equivalent bending stiffness of double-skin hollowed rectangular plates. For this purpose, the equivalent bending stiffness of the plate are expressed first in the quadratic polynomial form with respect to the design parameters for structural optimization by using the Response Surface Method (RSM). Finite element formulation for bending problem of the plate is also formulated by using the ACM rectangular element, and then FE source code is developed by incorporating the equivalent stiffness obtained by the RSM. Finally the numerical results obtained from the present FEA with the equivalent stiffness are compared with the ones by a commercial FE software, ANSYS, and then the applicability of the approximate equivalent stiffness are studied.